Modification of Leaf Glucosinolate Contents in Brassica oleracea by Divergent Selection and Effect on Expression of Genes Controlling Glucosinolate Pathway - Sotelo, Tamara; Velasco, Pablo; Soengas, Pilar; Rodríguez, Víctor M.; Cartea, María E. (Frontiers in Plant Science, 2016)
Modification of the content of secondary metabolites opens the possibility of obtaining vegetables enriched in these compounds related to plant defense and human health. We report the first results of a divergent selection for glucosinolate (GSL) content of the three major GSL in leaves: sinigrin (SIN), glucoiberin (GIB), and glucobrassicin (GBS) in order to develop six kale genotypes (Brassica oleracea var. acephala) with high (HSIN, HIGIB, HGBS) and low (LSIN, LGIB, LGBS) content. The aims were to determine if the three divergent selections were successful in leaves, how each divergent selection affected the content of the same GSLs in flower buds and seeds and to determine which genes would be involved in the modification of the content of the three GSL studied. The content of SIN and GIB after three cycles of divergent selection increased 52.5% and 77.68%, and decreased 51.9% and 45.33%, respectively. The divergent selection for GBS content was only successful and significant for decreasing the concentration, with a reduction of 39.04%. Mass selection is an efficient way of modifying the concentration of individual GSLs. Divergent selections realized in leaves had a side effect in the GSL contents of flower buds and seeds due to the novo synthesis in these organs and/or translocation from leaves. The results obtained suggest that modification in the SIN and GIB concentration by selection is related to the GSL-ALK locus. We suggest that this locus could be related with the indirect response found in the GBS concentration. Meantime, variations in the CYP81F2 gene expression could be the responsible of the variations in GBS content. The genotypes obtained in this study can be used as valuable materials for undertaking basic studies about the biological effects of the major GSLs present in kales.